1985
DOI: 10.3133/wsp2256b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-level dams on the distribution of sediment, trace metals, and organic substances in the lower Schuylkill River basin, Pennsylvania

Abstract: PREFACEIn 1973, the U.S. Geological Survey began a series of intensive river-quality assessments designed to demonstrate the use of river-quality studies in basin planning and water-resources management. The first of these assessments was conducted in the Willamette River basin, Oregon. Others have been completed in the Yampa River basin, Colorado and Wyoming; the Chattahoochee River basin, Georgia; the Apalachicola River basin, Florida; the Truckee and Carson River basins, California and Nevada; and the Potom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…As a result, many regions have experienced similar consequences on sediment transport and Hg export. Numerous studies have shown that the dam construction has led to decreased sediment supply and altered trace metals or Hg dynamics in various regions, including the United States (Yorke et al, 1985), Europe (Eiriksdottir et al, 2017), Russia (Zolkos et al, 2022), and South America (Pestana et al, 2019). Considering that river export constitutes the largest source of Hg to coastal oceans (M. D. Liu et al, 2021), and with continuous planning and construction of dam programs, we suggest that future long-term data collection and modeling become imperative to fully understand the impacts of river damming on the deposition and cycling of Hg in coastal zones.…”
Section: Burial Flux Of Mercurymentioning
confidence: 99%
“…As a result, many regions have experienced similar consequences on sediment transport and Hg export. Numerous studies have shown that the dam construction has led to decreased sediment supply and altered trace metals or Hg dynamics in various regions, including the United States (Yorke et al, 1985), Europe (Eiriksdottir et al, 2017), Russia (Zolkos et al, 2022), and South America (Pestana et al, 2019). Considering that river export constitutes the largest source of Hg to coastal oceans (M. D. Liu et al, 2021), and with continuous planning and construction of dam programs, we suggest that future long-term data collection and modeling become imperative to fully understand the impacts of river damming on the deposition and cycling of Hg in coastal zones.…”
Section: Burial Flux Of Mercurymentioning
confidence: 99%